Gestión de información pública exigida por la LOTAIP en el GAD de Babahoyo - Montero Bastidas, Jhonny Alejandro (2019)
The objective of this case study is to identify the inadequate information management required by the LOTAIP in the Municipal GAD of the Babahoyo canton, an institution public dedicated to meet the needs of the population of Fluminense; these aspects are reflect at the time of delivery of relevant information outside the deadline by who requests it, situations that affect the availability of information to act as established by LOTAIP. Which requires the public entities of Ecuador to give get to know citizens relevant and pertinent information through the webpage of the same; was created with the aim of guaranteeing the right to information transparency and act as a mechanism exercising democratic participation